The Role of ICT in Skilled Manpower Development: A Study of Plateau State Polytechnic, Barkin-Ladi Nigeria - Dajang, Innocent Nasuk; Ayuba, Mandong Mathias; Dang, Samuel Mahanan (The Indonesian Institute of Science and Technology Research, 2024)
Information and Communication Technology (ICT) in workforce development is an essential and rapidly growing study area. An increasing number of countries are now undertaking training to develop skills in the use of ICT in teaching and other school activities to ensure higher efficiency, higher productivity, and higher educational outcomes, including quality of cognitive, creative, and innovative thinking. Against this backdrop, this study examined the role of ICT in skilled workforce development in polytechnics with Plateau State Polytechnic, Barkin–Ladi as the focus. Using the WhatsApp platform, a focus group discussion was conducted with eighteen academic staff members of the Department of General Studies of the Plateau State Polytechnic for data collection. The theoretical framework adopted for the study was the Computer-Aided Language Learning (CALL). Amongst other findings, the study discovered that computers and the internet have become indispensable worldwide and have frequently aided the training of skilled workforce and the creation of jobs and economic growth. It concluded that using ICT in lecture preparation and presentation, instructional delivery, individualized learning, collaboration, and evaluation of learning will significantly benefit our society in skilled workforce development for nation-building.